PIVKA-II plasma levels as markers of subclinical vitamin K deficiency in term infants - Dituri, F; Buonocore, G; Pietravalle, A; Naddeo, F; Cortesi, M; Pasqualetti, P; Tataranno, M L; Agostino, R (The journal of maternal-fetal & neonatal medicine, 2012)
As the vitamin K content of human milk is low and the newborn infant's stores of vitamin K are small, vitamin K deficiency with hemorrhage in the newborn is a worldwide problem. Proteins Induced by Vitamin K Absence (PIVKA-II) are the inactive under-γ-carboxylated forms of vitamin K-dependent clotting factors and they could be useful in predicting subclinical vitamin K deficiency (VKD). To demonstrate that PIVKA-II are earlier markers of subclinical VKD than Prothrombin time (PT) in exclusively breast-fed newborns. A prospective, controlled, randomized study, including 53 term newborns receiving vitamin K prophylaxis (0.5 mg i.m.) at birth, was performed. At 30 days newborns were divided into three groups (G) receiving respectively: 25 μg/die of vitamin K (G I), 12 μg/die (G II) or placebo (G III). PIVKA-II and PT were measured on 30th and 90th days of life. G III and GII showed a significant increase in PIVKA-II from 30 to 90 days of life respectively from 2.6 to 4.7 (p = 0.001) and from 2.3 to 3.5 (p < 0.001). No significant changes were found in GI. PT showed no significant changes among groups. PT is a less sensitive marker than PIVKA II. Oral supplementation with 25 μg/die avoids an increase of PIVKA-II. Despite increased PIVKA-II do not mean an impending occurrence of bleeding, they highlight a subclinical VKD and its relative risk.